Internationalization of Higher Education: Considerations for Adult Education - Xiao, Jing (Alberta Journal of Educational Research, 2018)
Internationalization has increasingly become an integral part of higher education in the past few decades. This process has posed both opportunities and challenges for adult education in higher education settings. This paper reflects on the implications of internationalization of higher education for adult education. A brief overview of the meanings, purposes, and approaches of internationalization is presented to provide some background to the shifting context of higher education. By looking at the emerging forces shaping the reality of research and practice in higher education, this paper proposes that teaching and learning in universities could dedicate more concerted efforts to sustainable student mobility, internationalizing curricula for intercultural understanding, and enhancing international collaboration. Depuis quelques décennies, l’internationalisation fait de plus en plus partie intégrante de l’enseignement supérieur. Ce processus s’accompagne tant de possibilités intéressantes que de défis pour l’éducation des adultes dans le milieu de l’enseignement supérieur. Cet article porte sur les incidence qu’a, sur l’éducation des adultes, l’internationalisation de l’enseignement supérieur. Un aperçu du sens et des objectifs de l’internationalisation, ainsi que des approches à ce phénomène, offre un contexte à l’évolution des études supérieures. En posant un regard sur les forces émergentes qui façonnent la recherche et la pratique dans l’enseignement supérieur, cet article propose que l’enseignement et l’apprentissage dans les universités soient davantage axés sur la mobilité durable des étudiants, l’internationalisation des programmes d’études de sorte à promouvoir la compréhension interculturelle et l’amélioration de la collaboration internationale. Mots clés : éducation des adultes, internationalisation, enseignement supérieur, enseignement et apprentissage, mobilité des étudiants, collaboration internationale.